2001
DOI: 10.1021/np010367x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Pathway to the Cancer Chemopreventive Secoisolariciresinol Diglucoside−Hydroxymethyl Glutaryl Ester-Linked Lignan Oligomers in Flax (Linum usitatissimum) Seed

Abstract: Application of stable and radioisotope precursor/tracer experiments resulted in the identification of various phenylpropanoid, monolignol, and lignan metabolites involved in the biosynthesis of the cancer chemopreventive secoisolariciresinol diglucoside (SDG; 1)-containing ester-linked "polymer(s)" in flax (Linum usitatissimum) seed. Individual analysis of size-segregated flax seed capsules at five early stages of their development provided a metabolic profile of intermediates leading to "biopolymer" biosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(49 citation statements)
references
References 46 publications
1
47
0
1
Order By: Relevance
“…(Westcott and Muir, 1996a). Also It had been suggested that p-coumaric acid and ferulic acid glucosides were linked directly via ester linkage of their carboxyl groups to the glucosyl moiety of SDG as a terminal unit in SDG oligomers (Struijset al,2008) and were easily released by alkaline hydrolysis (Johnssonet al,2002;Ford et al,2001). The step followed by extraction is hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Westcott and Muir, 1996a). Also It had been suggested that p-coumaric acid and ferulic acid glucosides were linked directly via ester linkage of their carboxyl groups to the glucosyl moiety of SDG as a terminal unit in SDG oligomers (Struijset al,2008) and were easily released by alkaline hydrolysis (Johnssonet al,2002;Ford et al,2001). The step followed by extraction is hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…The level of SDG in flaxseed, 1-4% (w/w) (Eliassonet al, 2003), is 60-700 times higher than that in other edible plant parts (Ford et al, 2001).Variation in flaxseed lignan concentrations depend on the variety, location, and crop year (Westcott and Muir,1996b).Secoisolariciresinol (SECO) amount found in foods. Whole seed and ground flax typically contain between 0.7% and 1.9% SDG, which is approximately 77 to 209 mg SDG/tbsp of whole seed or 56 to 152 mg SDG/tbsp of ground flaxseed (Morris, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cofactor Binding-As in other NAD(P)H dependent reductases, PCBER_Pt1, PLR_Tp1, and IFR_Ms1 have completely conserved 11 GXXGXXG 19 (NAD(P)H-binding motif) sequences (Fig. 3A, highlighted in red) at the first ␤-␣-␤ unit.…”
Section: Resultsmentioning
confidence: 99%
“…For example, PLRs, which catalyze reduction of the 8 -8Ј linked lignan pinoresinol (Scheme 1, structure 1) (6,10), generate the precursors of cancer-preventative natural products, such as secoisolariciresinol diglucoside (structure 2) derivatives in flaxseed (Linum usitatissimum) (11,12) and matairesinol (structure 3)/secoisolariciresinol (structure 4) in a wide variety of plant species (5,11,13). Such lignans are considered to be metabolized in mammals into the cancer-preventing "mammalian" lignans, enterodiol (structure 5) and enterolactone (structure 6), with the latter metabolites being generated in the gut by the action of gastrointestinal flora such as Clostridia sp (14,15).…”
mentioning
confidence: 99%
“…However, in certain other plant species, such as flax (Linum usitatissimum), the opposite stereoselective and enantiospecific transformations can predominate (16,19,20,42), i.e. whereby (Ϫ)-pinoresinol (11b) is preferentially formed and then metabolized into (Ϫ)-lariciresinol (12b) and (ϩ)-secoisolariciresinol (2b), respectively.…”
mentioning
confidence: 99%